Regulating lithium affinity of hosts for reversible lithium metal batteries - Liu, Hao; Ji, Yuchen; Li, Yang; Zheng, Shisheng; Dong, Zihang; Yang, Kai; Cao, Aimin; Huang, Yuxiang; Wang, Yinchao; Shen, Haifeng; Zhang, Shao‐jian; Pan, Feng; et al. (Interdisciplinary materials (Print), 2024)
Lithium (Li) metal batteries are regarded as the “holy grail” of next‐generation rechargeable batteries, but the poor redox reversibility of Li anode hinders its practical applications. While extensive studies have been carried out to design lithiophilic substrates for facile Li plating, their effects on Li stripping are often neglected. In this study, by homogeneously loading indium (In) single atoms on N‐doped graphene via In‐N bonds, the affinity between Li and hosting substrates is regulated. In situ observation of Li deposition/stripping processes shows that compared with the N‐doped graphene substrate, the introduction of In effectively promotes its reversibility of Li redox, achieving a dendrite‐free Li anode with much‐improved coulombic efficiency. Interestingly, theoretical calculations demonstrate that In atoms have actually made the substrate less lithophilic via passivating the N sites to avoid the formation of irreversible Li–N bonding. Therefore, a “volcano curve” for reversible Li redox processes is proposed: the affinity of substrates toward Li should be optimized to a moderate value, where the balance for both Li plating and Li stripping processes could be reached. By demonstrating a crucial design principle for Li metal hosting substrates, our finding could trigger the rapid development of related research. Through homogeneously incorporating indium (In) atoms onto N‐doped graphene via In–N bonds, Li‐substrate interaction is precisely tailored. In situ monitoring reveals enhanced reversibility of Li redox reactions with In, reducing lithophilicity and inhibiting irreversible Li–N bond formation. This proposes a “volcano curve” framework for optimizing substrate‐Li affinity, achieving balanced plating and stripping processes of Li metal anode.